2020
DOI: 10.3892/ol.2020.11391
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nine‑lncRNA signature as a novel prognostic marker of estrogen receptor‑negative breast cancer

Abstract: Long non-coding RNAs (lncRNAs) have been demonstrated to be aberrantly expressed in several types of tumor, and dysregulated lncRNAs are suggested to play a prognostic role in breast cancer (BC). Estrogen receptor (ER) status is a prognostic factor in patients with ER-negative BC, which is associated with poor prognosis. Thus, the present study developed a prognostic lncRNA signature specifically for ER-negative BC, in order to predict the risk of post-surgery relapse and improve patient prognosis. A gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Historically, heterogeneity in breast cancer is understood in terms of varying expression of the ER, PR, and HER2. Recent studies have supported the link between miRNAs and lncRNAs and HR expression in patients with BRCA, highlighting their potential as prognostic biomarkers in hormonal-dependent cancers ( 81 83 ). In the whole BRCA cohort, KDM7A-DT overexpression is associated with poor BRCA outcomes across the entire BRCA cohort.…”
Section: Discussionmentioning
confidence: 94%
“…Historically, heterogeneity in breast cancer is understood in terms of varying expression of the ER, PR, and HER2. Recent studies have supported the link between miRNAs and lncRNAs and HR expression in patients with BRCA, highlighting their potential as prognostic biomarkers in hormonal-dependent cancers ( 81 83 ). In the whole BRCA cohort, KDM7A-DT overexpression is associated with poor BRCA outcomes across the entire BRCA cohort.…”
Section: Discussionmentioning
confidence: 94%
“…The abnormal expression of linc02544 was reported in several diseases [ 12 , 13 ]. For instance, a study performed RNA sequencing and acquired many differently expressed lncRNAs, mRNAs, and circRNAs in the human hypertrophic scar, in which linc02544 was one of the top three deregulated expression lncRNAs, which may play a central role in hypertrophic scar [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of linc02544 was observed in several diseases, such as hypertrophic scars [ 12 ] and breast cancer [ 13 ]. A recent study identified numerous lncRNAs and mRNAs in lung adenocarcinoma, among which include linc02544 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%